Structural styles and linkage evolution in the middle segment of a strike-slip fault: A case from the Tarim Basin, NW China. (April 2022) - Shen, Zhuoyi; Neng, Yuan; Han, Jun; Huang, Cheng; Zhu, Xiuxiang; Chen, Ping; Li, Qiqi
Abstract: The structural geometric and kinematic analysis of the Shunbei No. 5 fault zone (fault SB5) in the Tarim Basin was conducted based on the fault interpretation on the three-dimensional (3D) seismic sections and coherence slices of several seismic reflecting surfaces in the study area. The fault SB5 evolution model was recovered using the fault pattern analyses and palaeostress reconstruction, which required factors like the width of the damage zone, maximum throw of the main fault, vertical separation, and the shear crack angle along the fault zone. The results show that: (1) Four tectonic layers in the vertical direction are identified according to the difference of structure style, divided by the top and bottom of the Cambrian salt rocks, and the top surface of the Ordovician carbonate. (2) Strike-slip faults in the study area are the middle segment of the large strike-slip fault zone composed of major faults and overlap zones; 11 stepovers in the study area can be classified into three types according to their geometric characteristics. Strain concentration appears on the overlap zone under the continuous shear stress field and shows high activity. Fault SB5 has undergone three major evolutionary stages: the transpressional stage in the Middle Ordovician, the dextral shearing stage in the Early Silurian, and the final evolutionary sinistral process in the Late Devonian. Highlights: We study geometric and kinematic characteristics of the deep buried strike-slip fault zone with high-resolution 3D seismic data. We identified four tectonic layers of strike-slip fault according to the seismic section. Three types of stepovers develops in the middle segment of strike-slip fault in the study area. We conduct the research of fault evolution stages and growth path based on the geometry pattern and pale-stress analyses.